The reality of organizational integrity and its impact on the relationship between organizational trust and organizational performance - Lecturer. Dr. Jasim Saad Jasim (Global Scientific Publishing, 2024)
The main research problem is the importance of studying the reality of organizational integrity for sports clubs ' administrations and its impact on achieving the dimensions of organizational trust to improve their position in society, raise their competitiveness, make their outputs distinguished by quality, increase the degrees of loyalty and affiliation among their employees to raise their performance level. This research aims to find out the interactive impact of organizational integrity on the relationship between organizational trust and organizational performance among members of administrative bodies in Dhi Qar governorate and measure the levels of variables studied. the research was conducted on an intentional sample composed of members of the administrative bodies of sports clubs Dhi Qar football governorate, where distributed (133) a questionnaire designed by the researcher after analyzing the results, it turned out that the respondents ' results were high in terms of organizational integrity, as the members of the governing bodies have a high level of perception of the extent to which club administrations apply them, not to mention the development of the relationship between organizational trust and the organizational performance of members of sports bodies, and the most important recommendations are the focus of sports clubs administrations on practicing organizational integrity behaviors because they have a significant impact on strengthening organizational trust and its reflection on the requirements of organization performance equality
Keywords: Organizational integrity; Organizational trust; Organizational performance